Using the secretome of mesenchymal progenitors of the umbilical cord as a modulator of neural and glial survival, viability and differentiation - Teixeira, F. G. (2012)
Although it is hypothesized that mesenchymal stem cells’ secretome plays a major role in CNS regeneration, little is known on the mechanisms that regulate these actions. In the present work we aimed to assess if the secretome of a population of MSCs isolated from the WJ of the UC (HUCPVCs) was able to modulate neural/glial survival differentiation and proliferation in in vitro and in vivo models. Two approaches were used: (1) primary cultures of neurons and glial cells, were incubated with conditioned media (CM) from HUCPVCs and (2) HUCPVCs or their CM were injected in the dentate gyrus of male Wistar rats. In vitro results revealed that HUCPVCs CM increased cell proliferation in neuronal and glial cells cultures, as well as the survival of astrocytes, oligodendrocytes and neurons. In vivo experiments revealed that animals injected with HUCPVCs, had an increased endogenous cell proliferation, and disclosed higher levels of FGF-2, BDNF and NGF, as indicated by qRT-PCR. On the other hand, in the animals injected with CM, the effect caused in the DG was more evident for astrocytes and neuronal cell densities. The CM was also able to induce the differentiation of resident neural precursor towards the neuronal lineages. With this work it was possible to show that HUCPVCs secretome is able to modulate in vitro and in vivo neural/glial cell survival proliferation and differentiation, a fact that may facilitate the future applications of these cells in future CNS related therapies.